2013
DOI: 10.1093/humrep/det349
|View full text |Cite
|
Sign up to set email alerts
|

Circulating insulin-like factor 3 (INSL3) in healthy and infertile women

Abstract: The present retrospective study was largely supported by departmental funds. There were no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…INSL3 has been suggested as a laboratory test that can be used in the diagnosis of PCOS (16,48). However, these studies were conducted with adult women.…”
Section: Discussionmentioning
confidence: 99%
“…INSL3 has been suggested as a laboratory test that can be used in the diagnosis of PCOS (16,48). However, these studies were conducted with adult women.…”
Section: Discussionmentioning
confidence: 99%
“…Free testosterone level (pmol/L) was calculated with the formula serum testosterone (nmol/L) × 10 × [2.28–1.38 × log( SHBG (nmol/L) × 0.1)]. INSL3 was measured using an established and well-validated time-resolved fluorescent immunoassay [27], modified for higher sensitivity [28]. The LOD was 10 pg/mL, with intra- and interplate CVs across the range of measurement of < 3 and < 10%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in cohorts of adult women suggest that INSL3 plasma levels are indicative of the number of ovarian antral follicles recruited and growing within a follicular wave (AnandIvell et al, 2013). As INSL3 is a product of the thecal cells of ovarian follicles, plasma INSL3 levels have been investigated and shown to be elevated in polycystic ovary syndrome, a common female endocrine disorder characterized by excessive production of androgens from ovarian follicles (Gambineri et al, 2007;Szydlarska et al, 2012;Anand-Ivell et al, 2013). Importantly, a recent study in cows demonstrated that INSL3 has a positive autoregulatory role in maintaining thecal androgen production that is essential for normal ovarian follicle development (Glister et al, 2013).…”
mentioning
confidence: 99%